A Palladium-Catalyzed Domino Reaction as Key Step for the Synthesis of Functionalized Aromatic Amino Acids - Stark, Tina; Suhartono, Marcel; Göbel, Michael W.; Lautens, Mark (Synlett, 2013)
A variety of substituted aromatic systems are synthesized by the Catellani reaction. These are used as precursors for novel amino acids with a basic side chain.
Keywords: C–H activation; artificial amino acids; asymmetric synthesis; norbornene; Catellani reaction